2020
DOI: 10.1002/ehf2.12902
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive individual patient data meta‐analysis of the effects of cardiac contractility modulation on functional capacity and heart failure‐related quality of life

Abstract: Aims Cardiac contractility modulation, also referred to as CCM ™ , has emerged as a promising device treatment for heart failure (HF) in patients not indicated for cardiac resynchronization therapy. We performed a comprehensive individual patient data meta-analysis of all non-confounded prospective randomized controlled trials of CCM vs. control that have measured functional capacity and/or quality of life questionnaires in patients with HF. Methods and results The Cochrane Central Register of Controlled Trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 45 publications
(87 reference statements)
1
32
0
4
Order By: Relevance
“…A recently performed individual‐patient meta‐analysis of 861 patients from randomized trials of CCM therapy 7 also demonstrated improvements in peak VO 2 , 6‐ min walk distance, and quality of life, thus confirming the findings of the present study. Moreover, long‐term improvements in quality of life, as estimated by NYHA class and MLWHFQ, along with reductions in rates of hospitalization were seen in another analysis 8 of 140 patients with LVEF of 25–45% included in the European Union Registry of CCM therapy.…”
Section: Discussionsupporting
confidence: 90%
“…A recently performed individual‐patient meta‐analysis of 861 patients from randomized trials of CCM therapy 7 also demonstrated improvements in peak VO 2 , 6‐ min walk distance, and quality of life, thus confirming the findings of the present study. Moreover, long‐term improvements in quality of life, as estimated by NYHA class and MLWHFQ, along with reductions in rates of hospitalization were seen in another analysis 8 of 140 patients with LVEF of 25–45% included in the European Union Registry of CCM therapy.…”
Section: Discussionsupporting
confidence: 90%
“…This large and long-term registry confirms effectiveness and benefits of CCM with the results of prior shorter-term and smaller randomized and registry studies. 5,6 Similar improvements in functional status and quality of life were shown for the AF and LVEF subgroups. LVEF improvements were also seen in all subgroups, with the largest improvements in patients of the lowest LVEF subgroup (≤25%).…”
Section: Discussionmentioning
confidence: 59%
“…This large and long‐term registry confirms effectiveness and benefits of CCM therapy in patients with moderate to severe heart failure consistent with the results of prior shorter‐term and smaller randomized and registry studies. 5 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…The core component of cardiac rehabilitation is the assessment of patient' class of risk [69] together with dietary advice [70,71], educational intervention [72,73], psychological support [74], exercise training [75] and therapy management [69]. Nowadays great progresses have been made in drug therapy [76][77][78][79][80], devices [81][82][83][84][85][86], and diagnostic technologies [87][88][89][90], which allow for an even greater reduction of some risk factors. However, to further reduce risk of new CV events, it is important to act not only on optimization of therapy and its adherence, but also on other risk factors such as OB and lifestyle [91][92][93].…”
Section: Exercise Training In Secondary CV Preventionmentioning
confidence: 99%